A study to evaluate the diagnostic value investigations in early diagnosis of septicemia in newborn - Sreedhar, S. V. S.; Qureshi, Mohammed Mujtaba (International Journal of Contemporary Pediatrics, 2021)
Background: The early diagnosis of neonatal septicemia still poses great difficulties. Early clinical symptomatology of neonatal septicemia is mimicked by a lot of other disorders affecting the newborn. To study the diagnostic value of the combination of CRP, absolute neutrophil count, band form count to the total neutrophil ratio in early diagnosis of neonatal septicemia. Methods: A total 75 babies who got admitted to Mahavir institute of medical sciences between October 2018 to September 2019 (12) months were included in the study medical college hospital in a newborn with age less than 3 days and with well-defined maternal risk factors or clinical evidence of sepsis are included in the study. In all neonates, the blood sample was collected from a peripheral vein with all aseptic precautions, before administration of any antibiotic therapy. Results: A total 20 preterm babies (62.5%) were affected by septicemia.12 full-term babies (37.5%) were affected by septicemia. The sensitivity of a lab test is defined as the proportion of infants with proven sepsis in whom the result is abnormal. Specificity is the proportion of healthy infants in whom the result is normal. Conclusions. When both CRP and band form to mature neutrophil counts were positive the sensitivity and the negative predictive value were high compared to other combinations of two.